Factors affecting livestock predation by lions in Cameroon - Van Bommel, L.; Bij de Vaate, M. D.; De Boer, W. F.; De Iongh, H. H. (African journal of ecology, 2007)
Interviews were carried out in six villages south-west of Waza National Park, Cameroon, to investigate the impact of factors related to the occurrence of livestock raiding by lions. Data were analysed at the village and individual level. Livestock losses (cattle, sheep and/or goats) caused by lions differed between villages, ranging from eight to 232 animals per village per year, or 37 to 1115 US$ per livestock owner. At the village and individual level, season and distance to the park boundary were important factors determining the occurrence of livestock losses (R 2 > 0.81). In villages close to the park attacks occurred irrespective of season and predation was high, and in villages farther from the park attacks mainly occurred during the rainy season and predation was low. Owning a large number of animals and attempting to chase away lions during an attack also increased predation on both village and individual level. At individual level, predation increased with the combined ownership of cattle and sheep and/or goats. Herding methods could be changed to decrease livestock predation, for example herding livestock with more than one herder, or building bomas for cattle at night. [PUBLICATION ABSTRACT]